Setting out for digital social security - Weber, Enzo (Geneva, 2018)
"Platform work is increasing worldwide, leaving a serious lack of social protection. In spite of the international and flexible character of platform work, extending social security is feasible – if one is ready to explore new avenues. This article is on setting out for Digital Social Security."